Effect of intrinsic factors on growth of listeria monocytogenes in sliced deli turkey. - Roenbaugh, Tawnya Leigh (Kansas State University, 2011)
Intrinsic factors impact Listeria monocytogenes growth in ready-to-eat poultry products. Sliced deli turkey was formulated with in-going concentrations of 1.5% NaCl or 0.75% NaCl/0.75% KCl, 0 ppm or 200 ppm NaNO[subscript]2, and using 10% or 45% pump for a total of 8 treatments. Turkey roasts were sliced and inoculated with a 5-strain L. monocytogenes cocktail or peptone water (control), vacuum packaged, and stored at 4[degree]C. Treatments were sampled on days 0, 7, 14, 21, 28, 42, 63, and 91 of storage to determine L. monocytogenes mean log growth and aerobic plate count (APC). The pH, water activity, residual nitrite concentration, and percent fat, moisture, protein, and sodium were measured using control treatments on each sampling day. There was a nitrite by day and a percent pump by day interaction (P<0.05) for L. monocytogenes and APC populations. Listeria monocytogenes populations in treatments containing 200 ppm NaNO[subscript]2 were 0.70 to 2.39 log CFU/cm[superscript]2 lower compared with products formulated with 0 ppm NaNO[subscript]2. Using 10% pump reduced L. monocytogenes populations by 0.62 to 1.50 log CFU/cm[superscript]2 on days 7 to 28 and at day 63 compared with 45% pump treatments. Incorporating 1.5% NaCl or 0.75% NaCl/0.75% KCl into formulations did not affect (P>0.05) L. monocytogenes populations during storage. On days 7 through 91, APC populations were 0.76 to 2.96 log CFU/cm[superscript]2 lower with inclusion of 200 ppm NaNO[subscript]2 compared to 0 ppm NaNO[subscript]2. There was a treatment by day interaction (P<0.05) for L. monocytogenes populations and APC. The initial inoculum level of L. monocytogenes averaged 2.21 log CFU/cm[superscript]2 and was similar (P>0.05) for all treatments on day 0. Listeria monocytogenes populations increased (P<0.05) from day 0 to 14 by 1.30 to 5.04 log CFU/cm[superscript]2. Overall, L. monocytogenes populations increased during storage and by day 91 L. monocytogenes populations were similar regardless of NaNO[subscript]2 level used except for treatments formulated with 0.75% NaCl/0.75% KCl and 10% pump. Listeria monocytogenes and APC populations were influenced by nitrite concentration and percent pump, while inclusion of NaCl or NaCl/KCl did not affect L. monocytogenes growth during refrigerated storage in vacuum packed sliced deli turkey.
Keywords: Listeria monocytogenes; Salt; Deli turkey; Sodium nitrite; Percent pump; Intrinsic factors; Food Science (0359); Microbiology (0410)